Real-Time Implementation of Islanded Microgrid for Remote Areas - Monika Jain; Sushma Gupta; Deepika Masand; Gayatri Agnihotri; Shailendra Jain (Journal of Control Science and Engineering)
Islanding is a condition in which a microgrid or a portion of power grid, consisting of distributed generation (DG) sources, converter, and load, gets disconnected from the utility grid. Under this condition the DG sources in a microgrid must switch to a voltage control mode, in order to provide constant voltage to local loads. In grid connected mode, the microgrid works as current controller and injects power to the main grid, depending on the power generation and local load with suitable market policies. Providing constant voltage at a stable frequency with proper synchronization amongst each DG in a microgrid is a challenge. The complexity of such grid requires careful study and analysis before actual implementation. These challenges of microgrid are addressed using real time OPAL-RT simulation technology. Thus the paper describes an islanded microgrid with master slave controller for power balance, voltage/frequency regulation, and synchronization. Based on an advanced real-time platform named Real-Time Laboratory (RT-LAB), the impacts of the micro sources, load, and converters in an islanded microgrid is studied in this paper. The effectiveness of the proposed controller is analyzed through experimental results under balanced/unbalanced nonlinear loads condition.